2019
DOI: 10.1111/age.12831
|View full text |Cite
|
Sign up to set email alerts
|

Inferring the population structure of the Maghreb sheep breeds using a medium‐density SNP chip

Abstract: North Africa has a great diversity of indigenous sheep breeds whose origin is linked to its environmental characteristics and to certain historical events that took place in the region. To date, few genome-wide studies have been conducted to investigate the population structure of North African indigenous sheep. The objective of the present study was to provide a detailed assessment of the genetic structure and admixture patterns of six Maghreb sheep populations using the Illumina 50K Ovine BeadChip and compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 20 publications
(26 reference statements)
1
15
0
Order By: Relevance
“…The present-day sheep are the miscegenation result of these three ancestral gene pools, as depicted in Figure 5 b,c and as revealed by Ben Sassi-Zaidy et al [ 19 ], who studied the genetic structure of Tunisian native meat sheep using microsatellite markers. Ben Jemaa et al [ 46 ], inferring the population structure of some Mediterranean sheep using SNP markers, proved the ancestral relationship between the dairy Sicilo-Sarde breed, and the Italian Sarda and Comisana breeds and revealed the existence of three ancestral gene pool clusters in the genetic structure of the Sicilo-Sarde and other Mediterranean sheep. Furthermore, with SNP markers, Ciani et al [ 47 ] revealed the genetic differentiation of the two insular Sicilian and Sardinian Italian sheep from continental sheep populations, demonstrating the influence of the isolation of these breeds in preserving the ancestral genetic patterns, which reflect the historic maritime waves of sheep introduction to the Mediterranean area.…”
Section: Resultsmentioning
confidence: 99%
“…The present-day sheep are the miscegenation result of these three ancestral gene pools, as depicted in Figure 5 b,c and as revealed by Ben Sassi-Zaidy et al [ 19 ], who studied the genetic structure of Tunisian native meat sheep using microsatellite markers. Ben Jemaa et al [ 46 ], inferring the population structure of some Mediterranean sheep using SNP markers, proved the ancestral relationship between the dairy Sicilo-Sarde breed, and the Italian Sarda and Comisana breeds and revealed the existence of three ancestral gene pool clusters in the genetic structure of the Sicilo-Sarde and other Mediterranean sheep. Furthermore, with SNP markers, Ciani et al [ 47 ] revealed the genetic differentiation of the two insular Sicilian and Sardinian Italian sheep from continental sheep populations, demonstrating the influence of the isolation of these breeds in preserving the ancestral genetic patterns, which reflect the historic maritime waves of sheep introduction to the Mediterranean area.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, using single nucleotide polymorphisms, Belabdi et al [ 21 ] revealed a high level of homogenization, such that some breeds with different origins appeared to be genetically undistinguishable. In addition, Ben Jemaa et al [ 22 ] reported a pattern of multiple hybridization events within all North African sheep populations. Several investigations of the genetic structuration of goat breeds in North Africa resulted in similar results.…”
Section: Discussionmentioning
confidence: 99%
“…Genomics may offer a solution to inconsistencies in definition of breed type, which could consequently improve the inferences if our study were to be repeated in the future. Depending on species, breeds and locations, extent of influence from exotic (generally of European descent) breeds due to recent admixture has been found to range from negligible to predominant in local populations ( Leroy et al, 2012 ; Murray et al, 2013 ; Buzanskas et al, 2017 ; Selepe et al, 2018 ; Ben Jemaa et al, 2019 ; Zhang et al, 2019 ). Although incomparably more precise to assess genetic origins of individuals than other sources of information, molecular approaches are currently limited in their coverage of livestock populations.…”
Section: Discussionmentioning
confidence: 99%